Framing Moderasi Beragama dalam Khutbah Jumat NU Online sebagai Media Komunikasi Dakwah Digital - Muiz, Ahmad Habibul; Taufikkurrohman, Diki; Sattar, Abdullah (Indonesian Journal of Humanities and Social Sciences, 2025)
This study analyzes how NU Online frames Friday sermons as a medium of digital da’wah communication to foster awareness of religious moderation and reduce social polarization in Indonesia. Using a descriptive qualitative approach and Robert N. Entman’s Framing Theory, the study examines 3 sermon manuscripts through thematic coding techniques. While discourse on religious moderation is growing, few studies have focused specifically on Friday sermons as framing instruments in digital da’wah. The findings reveal that NU Online systematically defines the problem of intolerance, diagnoses its causes (narrow religious literacy, digital misinformation, weak character education), offers moral evaluations based on moderate Islamic values, and presents practical solutions such as strengthening social cohesion (ukhuwah) and ethical digital engagement. These sermons have proven to be effective transformative tools in shaping narratives of tolerance and enhancing inclusive, adaptive religious communication strategies in the digital era.